Novice and expert teachers' noticing of classroom management in whole-group and partner work activities: Evidence from teachers' gaze and identification of events. (August 2021) - Stahnke, Rebekka; Blömeke, Sigrid
Abstract: This eye-tracking study investigates how novice and expert teachers' noticing of classroom management events differs in two formats of instruction. 20 novices and 20 experts participated in the study, watching short video clips of whole-group and partner work teaching situations. Their retrospective verbal reports were analyzed for events identified as note-worthy along with their allocation of visual attention as indicators of their noticing. Experts noticed more classroom management events in the partner work format than novices. Furthermore, their noticing was characterized by a focus on student-related events. Similarly, their gaze prioritized students more than novices', particularly in the partner work format. In contrast, novice teachers' attention was more drawn to the teacher in both formats of instruction. The results show that expertise in teachers' noticing of classroom management is characterized by a focus on students with the partner work format being more challenging for novice teachers. Highlights: Eye-tracking was used to examine how teachers perceive classroom situations. Novice and expert teachers' noticing of classroom management was compared. Expertise was characterized by a focus on students. Noticing of experts and novices varied by instructional format. The partner work format was more challenging for novice teachers.